2001
DOI: 10.1074/jbc.m004113200
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of an Antiviral Peptide from HIV-1

Abstract: DP178, a synthetic peptide corresponding to a segment of the transmembrane envelope glycoprotein (gp41) of human immunodeficiency virus, type 1 (HIV-1), is a potent inhibitor of viral infection and virus-mediated cell-cell fusion. Nevertheless, DP178 does not contain gp41 coiled-coil cavity binding residues postulated to be essential for inhibiting HIV-1 entry. We find that DP178 inhibits phospholipid redistribution mediated by the HIV-1 envelope glycoprotein at a concentration 8 times greater than that of sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
141
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(152 citation statements)
references
References 89 publications
9
141
2
Order By: Relevance
“…Second, Nieva and co-workers (38,39) have shown that HIV gp41-derived peptides corresponding to a Trp-rich region that partially overlaps the C terminus of T20 destabilize model membranes, suggesting that the equivalent region in gp41 might participate in the actual process of membrane fusion. Third, HIV gp41-derived T20 has been shown to bind to phospholipid membranes (23). Fourth, as already mentioned, membrane anchoring by fusion to a transmembrane domain restores the inhibitory potency of the ANAA mutant of HIV gp41-derived T20 (24).…”
Section: The Increased Inhibitory Potency Of the C-terminally Octylatmentioning
confidence: 97%
See 1 more Smart Citation
“…Second, Nieva and co-workers (38,39) have shown that HIV gp41-derived peptides corresponding to a Trp-rich region that partially overlaps the C terminus of T20 destabilize model membranes, suggesting that the equivalent region in gp41 might participate in the actual process of membrane fusion. Third, HIV gp41-derived T20 has been shown to bind to phospholipid membranes (23). Fourth, as already mentioned, membrane anchoring by fusion to a transmembrane domain restores the inhibitory potency of the ANAA mutant of HIV gp41-derived T20 (24).…”
Section: The Increased Inhibitory Potency Of the C-terminally Octylatmentioning
confidence: 97%
“…However, the understanding of its detailed mechanism of inhibition has been hampered by the following. (i) T20 lacks the residues that bind to the coiled coil C-terminal cavity; (ii) the known crystal and solution structures of fragments of HIV or SIV gp41 ectodomains do not fully include the regions corresponding either to T20 or to its putative binding site at the N terminus of the coiled coil; and (iii) in addition to a primary target site within the N-terminal heptad repeat (21), T20 has been postulated to bind to a second site in gp41, presumably a non-specified region at the C terminus of the ectodomain close to the viral membrane (22,23). Indeed, that T20 acts in close proximity to the membrane is supported by the studies of von Laer and co-workers (24).…”
mentioning
confidence: 99%
“…1A. act at the water-lipid membrane interface so that this region of GP41 would lie close to the bilayer surface with the 2F5 epitope bending outward in a loop to join the CHR region NH 2 -terminal to it. DP178 also overlaps a portion of the tryptophan-rich region (residues 665-673) and has been recently implicated in membrane interactions (54). Although we and others have shown that the isolated peptide is largely disordered in solution, it is entirely plausible that it exists as a more highly helical structure in the membrane-bound state of native GP41.…”
Section: Figmentioning
confidence: 99%
“…ENF binding to HR1 is thought to compete with the folding of the HR2 domain onto HR1, thus preventing Env-mediated membrane fusion (1,5,17). Accordingly, viral variants selected both in vitro and in vivo in the presence of ENF carry resistance mutations in the HR1 domain (35,42).…”
Section: Acquired Human Immunodeficiency Virus Type 1(hiv-1) Resistanmentioning
confidence: 99%